Produzioni ceramiche da Hadrianopolis (Albania) con rivestimento rosso o rosso-bruno: importazioni e produzioni locali - Cingolani, Sofia; de Silva, Ludovica Xavier (Rei Cretariae Romanae Fautorum Acta, 2022)
The paper presents a group of red-brownish slipped fragments brought to light during the archaeological investigations carried out by the University of Macerata from 2011 to 2016 in the city of Hadrianopolis (Epirus, Albania). This group of selected findings shows how regional and local productions have imitated the most popular fine wares, imported especially from the Eastern Mediterranean, reproducing their shapes and applying a red-brownish glaze. Further analysis on this subject has provided us with enough data to divide the material into two main categories. Thus, it was possible to isolate a supposed regional/local production of ‘sigillata’, with specific morphological and technological features, from a group of red-brownish slipped fragments which has been associated with the local production of coarse ware pottery. This situation provides evidence of Hadrianopolis’ full inclusion in both maritime and internal exchange network between the 2nd and the 3rd century AD, framing the site in an Adriatic and, more generally, Mediterranean context and confirming the strong relations with the port of Brindisi and the Nikopolis-Apollonia commercial axis.